Binimetinib (MEK162) in recurrent low-grade serous ovarian cancer resistant to chemotherapy and hormonal treatment - Han, Chanhee (Gynecol Oncol Rep, 2018)
BACKGROUND: Management of advanced/recurrent low-grade serous ovarian carcinoma (LGOSC) is often challenging. Effective treatment options remain limited for hormone and chemotherapy-resistant LGSOC. CASE: A 65-year-old woman with recurrent widespread LGSOC harboring the KRAS-G12 V hotspot mutation experienced a dramatic clinical response to Binimetinib (MEK162), a mitogen-activated protein kinase (MEK) inhibitor, after failing multiple chemotherapy and hormonal treatments. An 81% reduction of target lesions by RECIST 1.1 over 31 months of response duration was confirmed with serial CT scans. Episodes of drug-related toxicity (pneumonitis) easily resolved without sequelae with the use of oral steroids. CONCLUSION: Binimetinib may present a new treatment option for hormone- and chemotherapy-resistant LGSOC harboring KRAS mutations.